Partitioning and sourcing of evapotranspiration using coupled MARMITES-MODFLOW model, La Mata catchment (Spain) - Francés, Alain P.; Lubczynski, Maciek W. (Frontiers in Water, 2023)
The new coupled MARMITES-MODFLOW (MM-MF) model, coupling land surface and soil zone domains with groundwater, is presented. It implements model-based partitioning and sourcing of subsurface evapotranspiration (ETss) as part of spatio-temporal water balance (WB). The partitioning of ETss involves its separation into evaporation (E) and transpiration (T), while the sourcing of E and T involves separation of each of the two into soil zone (Esoil and Tsoil) and groundwater (Eg and Tg) components. The objective of such development is to understand the system dynamics of a hard rock catchment with shallow water table, through spatio-temporal quantification of water fluxes and evaluation of their importance in water balances, focusing on the Eg and Tg components of ETss. The MM-MF model was applied in the small La Mata catchment (∼4.8 km2, Salamanca Province, Spain), characterized by semi-arid climate, granitic bedrock, shallow water table and sparse oak woodland. The WB confirmed dependence of groundwater exfiltration on gross recharge. Besides the infiltration, these two water fluxes, together with Esoil, constituted the largest subsurface water fluxes. The Eg was higher than the Tg, which is explained by low tree coverage (∼7%). Considering seasonal variability, Eg and Tg were larger in dry seasons than in wet season, when solar radiation was the largest and soil moisture the most depleted. A relevant observation with respect to tree transpiration was that during dry seasons, the decline of Tsoil, associated with the decline of soil moisture, was compensated by increase of Tg, even with continuously declining water table. However, in dry season, T was below the atmospheric evaporative demand, indicating that the groundwater uptake by the tree species of this study constituted a survival strategy and not a mechanism for continued plant growth. The presented MM-MF model allowed to analyze catchment water dynamics and water balance in detail, accounting separately for impacts of evaporation and transpiration on groundwater resources. With its unique capability of partitioning and sourcing of ETss, the MM-MF model is particularly suitable for mapping groundwater dependent ecosystems, but also for analyzing impacts of climate and land cover changes on groundwater resources.